The intraoperative use of augmented and mixed reality technology to improve surgical outcomes: A systematic review. Issue 6 (13th September 2022) - Bollen, Edward; Awad, Laura; Langridge, Benjamin; Butler, Peter E. M.
Abstract: Background: This systematic review aims to critically appraise the intraoperative use of augmented and mixed reality technology to improve surgical outcomes. Method: A literature search of PubMed, Scopus, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov and WHO ICTRP was performed in accordance with Cochrane Handbook for Systematic Reviews of Interventions. Results: This review included 94 studies on 2473 patients, comprising 78 studies on augmented reality and 16 on mixed reality. This technology has seen broad intraoperative application. Augmented and mixed reality can reduce operative duration, blood loss, and the duration of inpatient care. Current evidence shows that they achieve this most in percutaneous surgery. Conclusions: Augmented and mixed reality technology improve surgical outcomes by increasing navigational speed and reducing navigational error intraoperatively. However, they have technical limitations which are the subject of ongoing research. Further studies are necessary to define how this technology is best applied intraoperatively. Systematic Review Registration : PROSPERO CRD42020205892.